Combined aerobic/resistance/inspiratory muscle training as the 'optimum' exercise programme for patients with chronic heart failure: ARISTOS-HF randomized clinical trial. (2nd December 2020) - Laoutaris, Ioannis D; Piotrowicz, Ewa; Kallistratos, Manolis S; Dritsas, Athanasios; Dimaki, Niki; Miliopoulos, Dimitris; Andriopoulou, Maria; Manolis, Athanasios J; Volterrani, Maurizio; Piepoli, Massimo F; Coats, Andrew J S; Adamopoulos, Stamatis; et al.
Abstract: Aims: An 'optimum' universally agreed exercise programme for heart failure (HF) patients has not been found. ARISTOS-HF randomized clinical trial evaluates whether combined aerobic training (AT)/resistance training (RT)/inspiratory muscle training (IMT) (ARIS) is superior to AT/RT, AT/IMT or AT in improving aerobic capacity, left ventricular dimensions, and secondary functional outcomes. Methods and results: Eighty-eight patients of New York Heart Association II–III, left ventricular ejection fraction  ≤ 35% were randomized to an ARIS, AT/RT, AT/IMT, or AT group, exercising 3 times/week, 180 min/week for 12 weeks. Pre- and post-training, peakVO2 was evaluated with cardiopulmonary exercise testing, left ventricular dimensions using echocardiography, walking distance with the 6-min walk test (6MWT), quality of life by the Minnesota Living with HF Questionnaire (MLwHFQ), while a programme preference survey (PPS) was used. Seventy-four patients of [mean 95% (confidence interval, CI)] age 66.1 (64.3–67.9) years and peakVO2 17.3 (16.4–18.2) mL/kg/min were finally analysed. Between-group analysis showed a trend for increased peakVO2 (mL/kg/min) [mean contrasts (95% CI)] in the ARIS group [ARIS vs. AT/RT 1.71 (0.163–3.25)(.), vs. AT/IMT 1.50 (0.0152–2.99)(.), vs. AT 1.38 (−0.142 to 2.9)(.)], additional benefits in circulatory power (mL/kg/min⋅mmHg) [ARIS vs. AT/RT 376 (60.7–690)*, vs. AT/IMT 423 (121–725)*, vs. AT 345 (35.4–656)*], left ventricular end-systolic diameter (mm) [ARIS vs. AT/RT −2.11 (−3.65 to (−0.561))*, vs. AT −2.47 (−4.01 to (−0.929))**], 6MWT (m) [ARIS vs. AT/IMT 45.6 (18.3–72.9)**, vs. AT 55.2 (27.6–82.7)****], MLwHFQ [ARIS vs. AT/RT −7.79 (−11 to (−4.62))****, vs. AT −8.96 (−12.1 to (−5.84))****], and in PPS score [mean (95% CI)] [ARIS, 4.8 (4.7–5) vs. AT, 4.4 (4.2–4.7)*] [(.) P  ≤ 0.1; * P  ≤ 0.05; ** P  ≤ 0.01; *** P  ≤ 0.001; **** P  ≤ 0.0001]. Conclusion: ARISTOS-HF trial recommends exercise training for 180 min/week and supports the prescription of the ARIS training regime for HF patients (Clinical Trial Registration: http://www.clinicaltrials.gov . ARISTOS-HF Clinical Trial number, NCT03013270).